Historical and philosophical debate in teaching socially controversial issues (2016)
This paper aims to understand historical and teaching particularities of socially controversial and contentious issues. The introduction of these issues in the field of education is recent, an overview of various disciplines in school —History, in particular— allows defining the extent and the scope of their progress and teaching practices. The growing role of debate and discussion as learning tools for those issues is reviewed at the philosophical level of the educational goals from two perspectives: the knowledge in school teaching and the level of authority in the school.